Radiological Diagnosis and Approach: Glomus Tumour at Finger Tip - Taori, A; Sakhi, P; Malukani, K; Patel, K (Nepalese Journal of Radiology, 2014)
A Glomus tumor is a rare benign neoplasm arising from the glomus body which is a neuroarterial structure and mainly found under the nail, on the fingertip or in the foot. We present here a case of a 60 Year old female with a long history of pain in her left Index finger. She underwent radiological investigations of Skiagram Hand, High resolution ultrasonography with color Doppler of Local Region (Finger), and MRI Finger; thereby diagnosis of glomus tumor was made. Subsequently it was surgically removed; Histopathological result was consistent with glomus tumour. DOI: http://dx.doi.org/10.3126/njr.v4i1.11370 Nepalese Journal of Radiology, Vol.4(1) 2014: 52-55